Biogenic synthesis of silver nanoparticles; study of the effect of physicochemical parameters and application as nanosensor in the colorimetric detection of Hg2+ in water. Issue 8 (20th June 2016) - Omobayo Adio, Salawu; Basheer, Chanbasha; Zafarullah, Khan; Alsharaa, Abdulnaser; Siddiqui, Zia
ABSTRACT: This research demonstrates the ability of biogenic synthesised silver nanoparticles (AgNPs) to sensitively and selectively detect the presence of mercury (Hg 2+ ) in water. To achieve this, the following study investigated the synthesis of AgNPs using plant extract from basil and characterised the synthesised AgNPs using scanning electron microscopy, energy dispersive X-ray spectroscopy, UV-visible spectrophotometry, X-ray diffractometry and Fourier transform infrared spectroscopy. We studied the effect of various factors, such as broth concentration, precursor concentration, temperature, contact time and pH, on the synthesis of the nanoparticles. The synthesised AgNPs were then used in the colorimetric detection of Hg 2+ in water. The as-prepared AgNPs showed high selectivity to detect Hg 2+ alone compared to other cations and high sensitivity at different concentration of Hg 2+ . The limit of detection for Hg 2+ was 6.25 × 10 –8 mol/L (12 µg/L) indicating that these biogenic synthesised AgNPs represent a highly sensitive Hg 2+ detection tool.